Exploring integrated tertiary care for children from Nunavut: experiences of families and healthcare providers at the Aakuluk clinic in Ottawa, Canada - Maria Cherba; Nancy Mike; Gwen Healey Akearok; Melissa Weber; Vesa Basha; Brianne Cantwell; Christine Paquette Cannalonga; Yipeng Ge; Radha Jetty (International Journal of Circumpolar Health)
Children from circumpolar regions must travel long distances to southern tertiary care centres for specialised care. While there are initiatives underway to support care closer to home, medical travel remains a necessity for many families. The Aakuluk clinic has been operating since 2019 at a tertiary hospital in Ottawa, Canada, to provide care to children from Nunavut. The clinic team includes nurse case managers, physicians, social workers, interpreters, and several community partners. This project aimed to identify the strengths and the challenges of the clinic from the perspectives of parents and healthcare providers. The study was conducted in collaboration with healthcare professionals and community members and was guided by Inuit research approaches. Fifty-one participants (parents and healthcare providers) in Nunavut and Ottawa were interviewed. The main strengths and challenges of the clinic that were reported are related to the following themes: access to holistic care, supporting the role of Inuit professionals as part of the care team, and resources needed to continue offering programmes such as Aakuluk to Inuit families. From the perspectives of parents and healthcare providers, there are several components of the Aakuluk model that can be considered when developing services for Inuit families in other tertiary care centres.